Price elasticities and implied tax revenue for alcoholic beverages: Evidence from Poland, France and Spain - Benjamin Bittschi; Ines Fortin; Sebastian Koch; Richard Sellner; Simon Loretz; Gregor Zwirn (Austrian Institute of Economic Research (WIFO), 2019)
The study estimates the tax revenue effects of changes in alcohol excise taxes for Spain, France and Poland. In addition to excise tax and VAT revenue effects, the price pass-through and the impact on market volumes is estimated. The main parameters - the tax pass-through rate of excise duties to consumer prices and the price elasticities of demand for alcoholic beverages - are estimated via state-of-the-art econometric approaches based a combination of household-levels and macro data. In a first step, the literature survey finds very diverse estimates for price elasticities of alcoholic beverages. We find evidence that excise taxes are typically fully passed onto consumer prices. Using micro data at the household level, we find price elasticities of demand for Spain, France and Poland which are higher (in absolute terms) than those typically found in the literature. This implies that price increases lead to larger drops in sales volume and, thus, tax increases might not result in the expected additional tax revenues. A macro level estimation of the relation between excise tax rates and revenues confirms a Laffer-curve type relationship, i.e., tax revenues cease to increase if excise tax rates reach a certain threshold level. The empirical evidence in this study suggests that the tax rates for beer and wine are well below this revenue maximising saddle point, but the evidence is inconclusive for spirits in the countries in question. Using the simulation tool developed in this study, it is found that a 1 percent increase in the excise tax rates of each alcoholic beverage prevailing in 2017 in each of the countries will have the strongest negative effect on the market volumes of spirits, while for beer and wine these increases translate to by and large higher collected tax revenues. Noteworthily, in some scenarios excise tax increases result in decreases in VAT revenues due to a significant reduction in the higher value on-trade sales.
Keywords: 330; alcoholic beverages; excise taxation; VAT; price elasticity